1999
DOI: 10.1002/(sici)1521-4141(199908)29:08<2464::aid-immu2464>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Effect on parasite eradication ofPneumocystis carinii-specific antibodies produced in the presence or absence of CD4+ α β T lymphocytes

Abstract: The contribution of specific antibodies (Ab) to successful clearance of Pneumocystis carinii from host pulmonary tissues has received increasing attention. Sera collected from diseased recombinase‐activating gene (RAG)‐1–/–, TCRβxδ–/–, TCRβ–/– and Aβ–/– mutants as well as from aerogenic parasite‐exposed (aero) and intranasally (i.  n.) infected C57BL/6 mice were transferred to RAG‐1–/– mutants inoculated with freshly isolated parasites. All sera, except for RAG‐1–/– serum, contained P. carinii‐specific Ab of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Clinical observations have shown that ␥␦-TCR ϩ T cells are elevated in blood and bronchoalveolar lavage (BAL) fluid of individuals with AIDS and P. carinii pneumonia (1,13), although the functional aspects of ␥␦-TCR ϩ T cells in these studies were not studied. Data from prior experimental studies have shown that ␥␦-TCR ϩ T-cell-deficient mice are not permissive for longterm P. carinii infection (10), while another study suggests that ␥␦-TCR ϩ T cells provide residual host defense functions in ␣␤-TCR ϩ T-cell-deficient mice (9). In other models of infection, ␥␦-TCR ϩ T cells have varying roles.…”
mentioning
confidence: 99%
“…Clinical observations have shown that ␥␦-TCR ϩ T cells are elevated in blood and bronchoalveolar lavage (BAL) fluid of individuals with AIDS and P. carinii pneumonia (1,13), although the functional aspects of ␥␦-TCR ϩ T cells in these studies were not studied. Data from prior experimental studies have shown that ␥␦-TCR ϩ T-cell-deficient mice are not permissive for longterm P. carinii infection (10), while another study suggests that ␥␦-TCR ϩ T cells provide residual host defense functions in ␣␤-TCR ϩ T-cell-deficient mice (9). In other models of infection, ␥␦-TCR ϩ T cells have varying roles.…”
mentioning
confidence: 99%
“…Interestingly, mice challenged with PC and thereafter depleted of CD4 ϩ T cells have persistent anti-PC IgG and are able to resist infection given a subsequent exposure, suggesting that Ab-based immunity may be sufficient for preservation of anti-PC resistance in the setting of CD4 ϩ T cell deficiency (14). PC-directed Abs likely function through multiple mechanisms to increase host resistance to infection and have been shown to significantly potentiate alveolar macrophage anti-PC effector function in vitro (15)(16)(17). Though recent studies suggest that PC-specific IgG is not absolutely required for host resistance, Fc␥R-deficient mice clear PC organisms with delayed kinetics (18).…”
Section: P Neumocystis Carinii (Pc)mentioning
confidence: 99%
“…Although an indispensable role for CD4 + T cells in bacterial clearance is well established [37], it has also been suggested that, under certain circumstances, CD4 + T cell-mediated inflammatory responses contribute significantly to PC pneumonia pathogenesis [38]. Recent studies by Hori et al [39••] have suggested an important role for CD4 + CD25 + Tr cells in controlling excessive T cell-mediated inflammatory responses.…”
Section: Pneumocystis Cariniimentioning
confidence: 99%